L13 - y = 1 x 2-2 at (2 , 1 2 ). 7 If f (2) = 3 and f (2)...

Info iconThis preview shows pages 1–10. Sign up to view the full content.

View Full Document Right Arrow Icon
L13 – Product and Quotient Rules The Product Rule – If f and g are both differentiable, then d dx f ( x ) g ( x ) = 1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
If h ( x ) = ( x 2 + 5)( - 2 x 3 - x ), find h 0 (1). 2
Background image of page 2
The Quotient Rule – If f and g are both differentiable, then d dx f ( x ) g ( x ) = 3
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
If f ( x ) = 3 x 2 - 3 e x , find f 0 ( x ). 4
Background image of page 4
Find f 0 ( x ) if f ( x ) = 4 x x 2 + 1 . Find the equation of all horizontal tangent lines to f ( x ). 5
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
If f ( x ) = ( x - 2) 2 x , find f 0 ( x ). Where is the tangent line to f ( x ) parallel to 35 x + y = 4? 6
Background image of page 6
Find the equation of the normal line to
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 8
Background image of page 9

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 10
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: y = 1 x 2-2 at (2 , 1 2 ). 7 If f (2) = 3 and f (2) =-1, g (2) = 5 and g (2) = 1 3 , nd h ( x ) where h ( x ) = f ( x ) g ( x ) . 8 If h ( x ) = x 2-3 xf ( x ) , f (2) = 3, and f (2) = 1 2 , nd h (2). 9 At what point(s) do the tangent lines to y = x 3 + x 2 x pass through (2 ,-3)? 10...
View Full Document

This note was uploaded on 01/13/2010 for the course MAC 2311 taught by Professor All during the Fall '08 term at University of Florida.

Page1 / 10

L13 - y = 1 x 2-2 at (2 , 1 2 ). 7 If f (2) = 3 and f (2)...

This preview shows document pages 1 - 10. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online